Peningkatan Kesadaran dan Pengetahuan Masyarakat Tentang Sadari (Pemeriksaan Payudara Sendiri) Untuk Deteksi Dini Kanker Payudara Pada Remaja Putri di Pondok Pesantren Al Mabrur Semarang - Novita Nining Anggraini; Siti Nurjanah (Institut Nalanda, 2024)
Breast cancer is a serious health problem among women. Early detection is very important to improve prognosis and cure. However, there are still many women who do not realize the importance of having regular check-ups. In an effort to increase awareness of the importance of early detection of breast cancer, the practice of awareness is one of the simple steps that the community can take. The magnitude of the breast cancer problem in Indonesia can be seen from the breast cancer patients who come. Cancer is a scourge for everyone, and the tendency to increase its prevalence cannot be avoided. This fear arises because the death rate from cancer is very high. This happens not only in Indonesia but also in various countries. The incidence of breast cancer varies greatly throughout the world, in general breast cancer is more common in developed countries than in developing countries. The high death rate for breast cancer is caused by 70% of breast cancer sufferers coming to health facilities when they are already in an advanced stage. Based on Hospital Information System (SIRS) data (2021, the number of breast cancer sufferers in Central Java shows an increase. In 2021, breast cancer sufferers reached 8,287 people, while in 2022 it will reach 10,530 people. This number shows an increase of 27 percent, breast cancer is in first place in the last 10 years until 2021 and there is an increase in cases every year with a proportion of 40% of all cancers. The size of the breast cancer problem in Indonesia can be seen from breast cancer patients who come for treatment, where 60-70% of sufferers are already in stage III-IV, in fact many cases of breast cancer have attacked young women. Awareness is a form of initial education for breast cancer screening.